The impact of job contact networks on wages of rural–urban migrants in China: a switching regression approach - Long, Wenjin; Appleton, Simon; Song, Lina (Taylor & Francis (Routledge), 2017)
In nationally representative household data from the 2008 Chinese Rural to Urban Migration Survey, nearly two thirds of rural–urban migrants found their employment through family members, relatives, friends or acquaintances. This paper investigates why the use of social network to find jobs is so prevalent among rural–urban migrants in China, and whether migrants face a wage penalty as a result of adopting this job search method. Using a switch regression approach, we find evidence of positive selection effects of the use of networks on wages. Users of networks tend to be older, to have migrated longer ago and to be less educated. In addition, married workers and those from villages with more out-migrant are more likely to use networks, while those without local residential registration status are less likely. Controlling for selectivity, we find a large negative impact of network use on wages. Using job contacts brings access to urban employment, but at the cost of markedly lower wages.